A The Effect of Project-Based Microeconomics Learning on Problem-Solving Ability Viewed from Cognitive Style - Sulastri Rini Rindrayani; Nanis Hairunisya (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This study sought to ascertain the impact of project-based learning on cognitive style-based problem-solving abilities.The population was 70 students of the Economic Education Department at the University of Bhinneka PGRI. The experimental class with 35 students used the project-based method and the control class with 35 students used the discussion method. The data on field independent, field dependent, and problem-solving skills were gathered via a test utilizing a subjective test instrument. Two-way Anova was utilized for data analysis. The findings demonstrated that: 1) project-based learning significantly improved students' problem-solving abilities as compared to the discussion method. 2) Field Independent and Field Dependent cognitive types differed significantly. 3) The approach and cognitive style of problem-solving have a strong link. This research demonstrated how problem-solving abilities in Field Independent and Field Dependent students were efficiently fostered through project-based learning.